¿Qué es filosofía? ¿Y tú me lo preguntas? Filosofía... eres tú. Sobre la condición de la filosofía en el pensamiento del joven Heidegger - Garrido Periñán, Juan José (Bollettino Filosofico, 2020)
It is a burdensome and complex task the attempt to determine what is Philosophy for the young Heidegger. This task is also ambiguous in that it is considered unresolved and intricate due to its subsidiary link to factical life. On one hand, the purpose of this work lies in clarifying the hermeneutic situation of such ambiguity pertaining to the constitution of philosophy itself; on other hand it would come to providing a proactive horizon where philosophizing appears combined with an essential task explained as a vocation that wants to transform human life. Keywords: Authenticity, Existence, Heidegger, Philosophy, Transformation